Genetic assessment of the effect of red yeast (Sporidiobolus pararoseus) as a feed additive on mycotoxin toxicity in laying hens - Hosseini, Shahrbanou; Brenig, Bertram; Winitchakorn, Sunattinee; Kanmanee, Chanidapha; Srinual, Orranee; Tapingkae, Wanaporn; Gatphayak, Kesinee (Frontiers in Microbiology, 2023)
Toxic fungal species produce hazardous substances known as mycotoxins. Consumption of mycotoxin contaminated feed and food causes a variety of dangerous diseases and can even lead to death of animals and humans, raising global concerns for adverse health effects. To date, several strategies have been developed to counteract with mycotoxin contamination. Red yeast as a novel biological dietary agent is a promising strategy to eliminate mycotoxicity in living organisms. Poultry are most susceptible animals to mycotoxin contamination, as they are fed a mixture of grains and are at higher risk of co-exposure to multiple toxic fungal substances.Therefore, this study investigated the genetic mechanism underlying long-term feeding with red yeast supplementation in interaction with multiple mycotoxins using transcriptome profiling (RNA_Seq) in the liver of laying hens. The results showed a high number of significantly differentially expressed genes in liver of chicken fed with a diet contaminated with mycotoxins, whereas the number of significant expressed genes was considerably reduced when the diet was supplemented with red yeast. The expression of genes involved in the phase I (CYP1A1, CYP1A2) and phase II (GSTA2, GSTA3, MGST1) detoxification process was downregulated in animals fed with mycotoxins contaminated diet, indicating suppression of the detoxification mechanisms. However, genes involved in antioxidant defense (GSTO1), apoptosis process (DUSP8), and tumor suppressor (KIAA1324, FBXO47, NME6) were upregulated in mycotoxin exposed animals, suggesting activation of the antioxidant defense in response to mycotoxicity. Similarly, none of the detoxification genes were upregulated in hens fed with red yeast supplemented diet. However, neither genes involved in antioxidant defense nor tumor suppressor genes were expressed in the animals exposed to the red yeast supplemented feed, suggesting decreases the adsorption of biologically active mycotoxins in the liver of laying hens. We conclude that red yeast can act as a mycotoxin binder to decrease the adsorption of mycotoxins in the liver of laying hens and can be used as an effective strategy in the poultry feed industry to eliminate the adverse effects of mycotoxins for animals and increase food safety for human consumers.